Five new species of the Zethus spinosus species group (Hymenoptera, Vespidae, Eumeninae, Zethus) - Cruciol, Ana Helena; Noll, Fernando Barbosa; Stange, Lionel A.; Lopes, Rogério Botion (Zootaxa, 2026)
Among the Neotropical genera of Eumeninae, Zethus Fabricius, 1804, has the largest number of species and is divided into six subgenera in this region. The genus is further divided into 29 species groups, one of which is the Zethus spinosus group. This study provides a taxonomic review of the Zethus spinosus group based on external morphology with the objective of designating and describing five new species: Z. lioneli Cruciol & Lopes, sp. nov. from Bolívia, Z. platinotus Cruciol, Stange & Lopes, sp. nov. from Brazil, Z. platynotatus Cruciol, Stange & Lopes, sp. nov. from Bolívia, Z. semilunaris Cruciol, Stange & Lopes, sp. nov. from Brazil, and Z. semiplanus Cruciol & Lopes, sp. nov. from Argentina.